Minimally Invasive Technique for Spontaneous Intraparenchymal Hemorrhage - Raval, Himanshu; Shah, Kalpesh; Bhatt, Mona (Indian Journal of Neurosurgery, 2023)
Objective The aim of this study was to introduce a cost-effective and less invasive method for the evacuation of intraparenchymal hemorrhage (IPH).Background IPH in the presence or absence of intraventricular hemorrhage has severe morbidity and has almost 50% mortality whether the patient is managed surgically or medically. Development of minimally invasive surgical techniques offers better outcomes but requires the use of special instruments and a unique skill set that is costly and requires special training.Method We inserted infant feeding tube within the hematoma via the left Kocher's burr hole. We instilled 40,000 IU of urokinase serially at an 8 hours interval for 3 days to evacuate the left gangliocapsular hematoma.Result We have treated a 50 years old hypertensive male patient with left gangliocapsular IPH and right hemiparesis (power: ⅖ on admission). After a month, on follow-up, the patient was conscious and oriented with improved right hemiparesis (power: ⅘).Conclusion This technique of evacuating hematoma is instrumental in peripheral centers in developing as well as under-developed countries where there are limited resources and a better outcome is expected with minimal morbidity.
Keywords: IPH; urokinase; MIS